The Influence of TikTok Exposure on Gen Z Fashion Imitation Among University Students in Surabaya - Aldania, Salsabila; Yumna, Rahima; Ayattina, Rea (Journal Commedies, 2024)
Social media exerts a major influence on Gen Z students in Surabaya, particularly regarding the imitation of fashion styles featured on platforms such as TikTok. One notable influence is the account @cadburylemonade, known as "Mbak Tumbas." This study explores the impact of TikTok media exposure on dress style imitation behavior. The study involved 400 respondents from five public universities in Surabaya with a margin of error of 5%. The results indicate that information exposure has a positive effect on the level of confidence/trust. Based on the t-test, it was found that the calculated t-value is 7.245, which is greater than the t-table value of 1.966 (7.245 > 1.966); thus, it can be concluded that H1 is accepted. Understanding this phenomenon is crucial for developing effective strategies to interact with this demographic and to manage both the negative and positive impacts of these behavioral changes.